Decision Processes and Interactions During a Two-Woman Traverse of Antarctica - Atlis, Mera M.; Leon, Gloria R.; Sandal, Gro M.; Infante, Michael G. (Environment and Behavior, 2004)
This investigation assessed an international two-woman team engaged in a 97-day traverse of Antarctica. Measures consisted of preexpedition personality assessments; expedition weekly ratings of individual and team status and work performance; postexpedition semistructured interview. Both participants scored relatively highest on the Multidimensional Personality Questionnaire (MPQ) Absorption scale, the Personality Characteristics Inventory (PCI) Work and Positive Expressivity scales and lowest on the PCI Verbal Aggressiveness scale. One member reported sensed presence experiences, which served as an important motivating factor when fatigued or disappointed about daily progress. Enjoyment and awe of the environment were significant aspects of the daily trek and sources of psychological strength. Advantages of the co-equal dyad were evident in the cooperative nature of decision making and substantial similarities in approach to solving problems. Differences from the usual military command structure in decision-making processes and implications for planetary expeditions are discussed.
Keywords: Antarktis; kvinner; polarekspedisjoner; psykologi

Eight glacial cycles from an Antarctic ice core - Augustin, Laurent; Barbante, Carlo; Barnes, Piers R. F.; Marc Barnola, Jean; Bigler, Matthias; Castellano, Emiliano; Cattani, Olivier; Chappellaz, Jerome; Dahl-Jensen, Dorthe; Delmonte, Barbara; Dreyfus, Gabrielle; Durand, Gael; et al. (Nature, 2004)
The Antarctic Vostok ice core provided compelling evidence of the nature of climate, and of climate feedbacks, over the past 420,000 years. Marine records suggest that the amplitude of climate variability was smaller before that time, but such records are often poorly resolved. Moreover, it is not possible to infer the abundance of greenhouse gases in the atmosphere from marine records. Here we report the recovery of a deep ice core from Dome C, Antarctica, that provides a climate record for the past 740,000 years. For the four most recent glacial cycles, the data agree well with the record from Vostok. The earlier period, between 740,000 and 430,000 years ago, was characterized by less pronounced warmth in interglacial periods in Antarctica, but a higher proportion of each cycle was spent in the warm mode. The transition from glacial to interglacial conditions about 430,000 years ago (Termination V) resembles the transition into the present interglacial period in terms of the magnitude of change in temperatures and greenhouse gases, but there are significant differences in the patterns of change. The interglacial stage following Termination V was exceptionally long—28,000 years compared to, for example, the 12,000 years recorded so far in the present interglacial period. Given the similarities between this earlier warm period and today, our results may imply that without human intervention, a climate similar to the present one would extend well into the future.
Keywords: Antarktis; klimagasser; paleoklimatologi

Whaler's cross on Deception Island - Barr, Susan; Downie, Rod; Sánchez, Rodolfo (Polar Record, 2004)
The cemetery at Whalers Bay, Deception Island, was the largest in the Antarctic prior to being partially buried and partially washed away during a volcanic eruption in 1969. In 2002 a wooden cross at Argentina's Decepción Station was identified as being that of the Norwegian whaler Peder Knapstad. It was removed, secured in a base, and re-erected at Whalers Bay.
Keywords: Antarktis; Deceptionøya; Sørishavet; kulturminneforvaltning; kulturminner

Numerical simulation of three-dimensional, transient snow drifting around a cube - Beyers, Meiring; Sundsbø, Per Arne; Harms, Thomas M. (Journal of Wind Engineering and Industrial Aerodynamics, 2004)
This paper presents the results of the numerical simulation of drifting snow surrounding a simple 2m cubicle structure. These results are compared and verified against data from snow drifting experimental tests carried out at SANAE IV research station, Antarctica, during the summer research period of January 2002. In addition to the snow drifting field observations, wind profile data were also obtained from cup-type anemometers mounted on a 6m wind mast. These data were employed to derive the characteristic surface roughness, shear velocity and approaching wind profile functions. The present work numerically simulates a transient three-dimensional turbulent viscous flow in an Eulerian coordinate frame including snow advection. A modified turbulent wall law is employed that accounts for the effects of snow saltation on the effective aerodynamic surface roughness. The numerical simulation employed the commercial CFD code, FLOW-3D, with additional user Fortran coding added to model the snow entrainment, subsequent accumulation or erosion of snow as well as temporal snow surface changes. The snow accumulation and erosion model is presented and discussed. The snow accumulation predicted by this numerical simulation compares favourably with the experimental results obtained from the Antarctica field testing.
Keywords: Antarktis; forskningsstasjoner; geofysikk; ingeniørvitenskap; mekanikk; numerisk modellering

Slope failure dynamics and impacts from seafloor and shallow sub-seafloor geophysical data: case studies from the COSTA project - Canals, M.; Lastras, G.; Urgeles, R.; Casamor, J.L.; Mienert, Jürgen; Cattaneo, A.; De Batist, M.; Haflidason, Haflidi; Imbo, Y.; Laberg, J.S.; Locat, J.; Long, D.; et al. (COSTA - Continental Slope Stability, 2004)
Holocene and slightly pre-Holocene submarine landslide are found both in high-latitude glacial-dominated margins and in lower latitude, river-dominated margins. This paper constitutes a major assessment on some of the best-studied submarine instabilities in the world. We review and update from original data and literature reports the current state of knowledge of Storegga, Traenadjupet and Finneidfjord slides from the mid-Norwegian margin, Afen Slide from the Faeroe-Shetland Channel, BIG'95 Slide and Central Adriatic Deformation Belt (CADEB) from continental slope and inner continental shelf settings off the Ebro and Po rivers in the Mediterranean Sea, Canary Slide west of the westernmost, youngest Canary Islands and Gebra Slide off the northern tip of the Antarctic Peninsula in the southern hemisphere, i.e. those studied in the Continental Slope Stability (COSTA) project. The investigated slides range in size from the gigantic 90,000 km2 and almost 3000 km3 Storegga Slide to the tiny 1 km2 and 0.001 km3 Finneidfjord Slide. Not only do individual submarine landslides rarely involve processes precisely fitting with pre-established categories, mostly based on subaerial research, but also they display complex mechanical behaviors within the elastic and plastic fields. Individual events can involve simultaneous or successive vertical to translational movements including block detachment, block gliding, debris flow, mud flow and turbidity currents. The need for an in-depth revision of the classification criteria, and eventually for a new classification system, based on the new imaging capabilities provided by modern techniques, is more than obvious. We suggest a new system, which, for the moment, is restricted to debris flows and debris avalanches. Volume calculation methods are critically reviewed and the relations between some key geomorphic parameters are established for the selected slides. The assumed volume missing from scar areas does not necessarily match the actual volume of sediment remobilised by an individual event since in situ sediment can be remoulded and eventually incorporated during the slide downslope journey. CADEB, a shore-parallel prodelta detached from its source, is the exception to the good correlation found between across slope width and alongslope length with slide area. Height drop measured from the headwall upper rim to its foot correlates with the debris deposit maximum thickness unless the slide moves into restricted areas, which prevent farther forward expansion of the deposit, such as Gebra and BIG'95. In such cases, “over-thickened” deposits are found. A particularly loose and fluid behavior can be deduced for slides showing an “over-thinned” character, such as the Canary Slide that traveled 600 km. Scar areas and slip planes have been investigated with particular emphasis. Although slide headwalls might present locally steep gradients (up to 23° for Storegga Slide), the slope gradients of both the failed segment margins and the main slip planes are very low (max. 2° and usually around 1° and less). An exception is the Finneidfjord Slide (20°–<5°) that occurred in 1996 because of a combination of climatic and anthropogenic factors leading to excess pore pressure and failure. Mechanically distinct, low permeable clayey “weak layers” often correspond to slip planes beyond the slide headwall. Since not only formation of these “weak layers” but also sedimentation rates are climatically controlled, we can state that slide pre-conditioning is climatically driven too. Run-out distances reflect the degree of disintegration of the failed mass of sediment, the total volume of initially failed material and transport mechanisms, including hydroplanning. Commonly, specific run-outs could be attributed to distinct elements, such as cohesive blocks and looser matrix, as nicely illustrated by the BIG'95 Slide. Total run-outs usually correspond to matrix run-outs since the coarser elements tend to rest at shorter distances. Outrunner blocks are, finally, a very common feature proving the ability of those elements to glide over long distances with independence of the rest of the failed mass. In addition to pre-conditioning factors related to geological setting and sedimentation conditions, a final trigger is required for submarine landslides to take place, which is most often assumed to be an earthquake. In high latitude margins, earthquake magnitude intensification because of post-glacial isostatic rebound has likely played a major role in triggering landslides. Although it cannot be totally ruled out, there is little proof, at least amongst the COSTA slides, that gas hydrate destabilisation or other processes linked to the presence of shallow gas have acted as final triggers.
Keywords: Antarktis; batymetri; geofysikk; marin geologi

Fiskerier i Antarktis (6.4) - Dommasnes, Are; Iversen, Svein A; Løbach, Terje (Havets ressurser 2004 (Fisken og havet : Særnummer), 2004)
Keywords: Antarktis; fangst; fiskeindustri; fiskeriforskning; krill; ressurser

Antarktis: gamle gneiser og spektakulære granitter - Engvik, Ane K; Elvevold, Synnøve (Geo: energi & ressurser, 2004)
Keywords: Antarktis; Dronning Maud Land; geologi

Seasonal ventilation of the cavity beneath Filchner-Ronne Ice Shelf simulated with an isopycnic coordinate ocean model - Jenkins, Adrian; Holland, David M.; Nicholls, Keith W.; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
The ocean cavity beneath Filchner-Ronne Ice Shelf is observed to respond to the seasonal cycle of water mass production on the continental shelf of the southern Weddell Sea. Here we use a numerical model to investigate the propagation of newly formed shelf waters into the cavity. We find that the model reproduces the most distinctive features of the observed seasonality and offers a plausible explanation for those features. The most saline shelf waters are produced in the far west, where the inflow to the cavity peaks twice each year. The major peak occurs during the short period around midwinter when convection reaches full depth and the densest waters are generated. Once the surface density starts to decline, dynamic adjustment of the restratified water column leads to a gradual fall in the salinity at depth and a secondary peak in the inflow that occurs in summer at the western coast. Beneath the ice shelf the arrival of the wintertime inflow at the instrumented sites is accompanied by a rapid warming, while the slower decline in the inflow leads to a more gradual cooling. Water brought in by the secondary, summer peak flows mainly to the eastern parts of the cavity. Here the seasonality is suppressed because the new inflows mix with older waters that recirculate within a topographic depression. This pooling of waters in the east, where the primary outflow of Ice Shelf Water is generated, dampens the impact of seasonality on the local production of Weddell Sea Bottom Water.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi

Pole-to-pole validation of Envisat GOMOS ozone profiles using data from ground-based and balloon sonde measurements - Meijer, Yasjka; Swart, Daan P J; Allaart, M; Andersen, S B; Bodeker, G; Boyd, I; Braathen, Geir; Calisesi, Yasmine; Claude, H; Dorokhov, Valery; von der Gathen, P; Gil, M; et al. (Journal of Geophysical Research: Atmospheres, 2004)
In March 2002 the European Space Agency (ESA) launched the polar-orbiting environmental satellite Envisat. One of its nine instruments is the Global Ozone Monitoring by Occultation of Stars (GOMOS) instrument, which is a medium-resolution stellar occultation spectrometer measuring vertical profiles of ozone. In the first year after launch a large group of scientists performed additional measurements and validation activities to assess the quality of Envisat observations. In this paper, we present validation results of GOMOS ozone profiles from comparisons to microwave radiometer, balloon ozonesonde, and lidar measurements worldwide. Thirty-one instruments/launch sites at twenty-five stations ranging from the Arctic to the Antarctic joined in this activity. We identified 6747 collocated observations that were performed within an 800-km radius and a maximum 20-hour time difference of a satellite observation, for the period between 1 July 2002 and 1 April 2003. The GOMOS data analyzed here have been generated with a prototype processor that corresponds to version 4.02 of the operational GOMOS processor. The GOMOS data initially contained many obviously unrealistic values, most of which were successfully removed by imposing data quality criteria. Analyzing the effect of these criteria indicated, among other things, that for some specific stars, only less than 10% of their occultations yield an acceptable profile. The total number of useful collocated observations was reduced to 2502 because of GOMOS data unavailability, the imposed data quality criteria, and lack of altitude overlap. These collocated profiles were compared, and the results were analyzed for possible dependencies on several geophysical (e.g., latitude) and GOMOS observational (e.g., star characteristics) parameters. We find that GOMOS data quality is strongly dependent on the illumination of the limb through which the star is observed. Data measured under bright limb conditions, and to a certain extent also in twilight limb, should be used with caution, as their usability is doubtful. In dark limb the GOMOS data agree very well with the correlative data, and between 14- and 64-km altitude their differences only show a small (2.5–7.5%) insignificant negative bias with a standard deviation of 11–16% (19–63 km). This conclusion was demonstrated to be independent of the star temperature and magnitude and the latitudinal region of the GOMOS observation, with the exception of a slightly larger bias in the polar regions at altitudes between 35 and 45 km.
Keywords: Antarktis; fjernmåling; meteorologi; målinger; ozonlaget; polarområdene; stratosfæren

Circulation and water masses beneath the northern Ronne Ice Shelf, Antarctica - Nicholls, Keith W.; Makinson, Keith; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
We present oceanographic data from beneath the northern Ronne Ice Shelf. The data were collected during the austral summer of 2002–2003 from four sites located near the ice front in the Ronne Depression. They consist of conductivity-temperature-depth (CTD) profiles and time series from moored instruments that vary in length from 9 to 20 weeks. A strong, tidally modulated inflow of relatively fresh water was found at the eastern margin of the Ronne Depression. This low-density inflow powers high basal melt rates that are responsible for a substantially thinned area of ice shelf. A northward flow of Ice Shelf Water along the western margin of the depression (the Antarctic Peninsula coast) was inferred from the CTD data. From the new CTD and current meter data, and from published results from cruises along the ice front, we suggest that the flows at the margins of the Ronne Depression establish east-west density gradients that drive an anticyclonic circulation within the depression. The barotropic component of the circulation forms a gyre of strength 5 × 105 m3 s−1 and occupies a bowl in the field of water column thickness in the northern portion of the depression. All water masses sampled had temperatures below the surface freezing point and are therefore classified as Ice Shelf Water. The relatively complex nature of the oceanographic regime in the Ronne Depression is overlain by a seasonal variability that is hinted at by the available time series, probably explaining the apparent absence of inflowing HSSW at the time of the measurements.
Keywords: Antarktis; geofysikk; isfront; isshelf; oseanografi; vannmasser

Interannual variability and ventilation timescales in the ocean cavity beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
Multiyear time series of ocean current and temperatures from beneath Filchner-Ronne Ice Shelf, Antarctica, demonstrate both seasonal and interannual variability. The seasonal signal is visible at all measurement sites, although it was swamped for a 2-year period (1999–2001) when extraordinarily light sea-ice cover in the southern Weddell Sea during the 1997–1998 Austral summer caused an anomalously large pulse of High Salinity Shelf Water to flush beneath the ice shelf. The pulse was observed twice at an instrumented site near the Berkner Island coast, once on its way to the Filchner Depression and once after the signal had propagated around the depression and returned to the site as an anomalously large pulse of Ice Shelf Water. The timings of the signal allow an estimate of 24–30 months for the flushing timescales of the sub-ice shelf ocean cavity, indicating that the cavity is highly responsive to external forcing. A timescale for the full ventilation of the cavity of 4–5 years is obtained from the length of time the sub-ice shelf conditions take to return to their original state, a timescale significantly shorter than previous estimates.
Keywords: Antarktis; Weddellhavet; geofysikk; havstrømmer; oseanografi

Holocene climate in the Atlantic sector of the Southern Ocean: Controlled by insolation or oceanic circulation? - Nielsen, Simon Harder Holm; Koç, Nalân; Crosta, Xavier (Geology, 2004)
The Holocene climate of the Southern Ocean is not well understood, mainly because of the lack of high-resolution reconstructions of ocean surface properties. Here we present a 12,500-yr-long, decadal-scale record of Holocene sea-surface temperatures and sea- ice presence from the Polar Front of the East Atlantic Southern Ocean. The record shows gradual climate change, with no abrupt Neoglacial cooling, and an unprecedented late Holocene warming. The dominant forcing factor appears to be precessional insolation; Northern Hemisphere summer insolation correlates to at least the early to middle Holocene climate trend. Spectral analysis reveals centennial-scale cyclic climate changes with periods of 1220, 1070, 400, and 150 yr. The record shows good correlation to East Antarctic ice cores and to climate records from South Georgia and Bunger Oasis. However, the record shows out-of-phase behavior with regard to climate records from the western Antarctic Peninsula and the Peru-Chile Current; such behavior hints at a climatic divide through Patagonia, the Drake Passage, and between West and East Antarctica.
Keywords: Antarktis; Sørishavet; geologi; havis; klimaendringer; paleoklimatologi

Additions and corrections to the Lichens of Antarctica and South Georgia - Øvstedal, Dag; Smith, Ronald I. Lewis (Cryptogamie, Mycologie, 2004)
The taxonomic listing given in Lichens of Antarctica and South Georgia (Øvstedal & Lewis Smith 2001) has been updated. 17 additional taxa of lichenised fungi are described, including several nomenclatural changes. 14 of these are considered as new records for the Antarctic and one is new to South Georgia. One is described as new to science.
Keywords: Antarktis; biogeografi; botanikk; lav; planter; taksonomi

Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

Frazil ice formation in an ice shelf water plume - Smedsrud, Lars H.; Jenkins, Adrian (Journal of Geophysical Research: Oceans, 2004)
We present a model for the growth of frazil ice crystals and their accumulation as marine ice at the base of Antarctic ice shelves. The model describes the flow of buoyant water upward along the ice shelf base and includes the differential growth of a range of crystal sizes. Frazil ice formation starts when the rising plume becomes supercooled. Initially, the majority of crystals have a radius of ?0.3 mm and concentrations are below 0.1 g/L. Depending on the ice shelf slope, which controls the plume speed, frazil crystals increase in size and number. Typically, crystals up to 1.0 mm in radius are kept in suspension, and concentrations reach a maximum of 0.4 g/L. The frazil ice in suspension decreases the plume density and thus increases the plume speed. Larger crystals precipitate upward onto the ice shelf base first, with smaller crystals following as the plume slows down. In this way, marine ice is formed at rates of up to 4 m/yr in some places, consistent with areas of observed basal accumulation on Filchner-Ronne Ice Shelf. The plume continues below the ice shelf as long as it is buoyant. If the plume reaches the ice front, its rapid rise produces high supercooling and the ice crystals attain a radius of several millimeters before reaching the surface. Similar ice crystals have been trawled at depth north of Antarctic ice shelves, but otherwise no observations exist to verify these first predictions of ice crystal sizes and volumes.
Keywords: Antarktis; geofysikk; glasiologi; numerisk modellering; oseanografi

Ozone loss rates over the Arctic 2002/03 and Antarctic 2003 measured with the Match approach - Streibel, Martin; von der Gathen, P; Rex, M; Deckelmann, H; Harris, N; Braathen, G; Chipperfield, M; Millard, G; Reimer, E; Alfier, R; Allaart, M; Andersen, S; et al. (2004)
To improve our understanding of wintertime polar ozone losses, two ozonesonde Match campaigns were performed. The first one was carried out in the Arctic winter 2002/03. About 450 coordinated ozonesondes were launched from late November 2002 to March 2003. Temperatures low enough for the formation of polar stratospheric clouds (PSC) occurred already in the second half of November. At 475 K the Match analysis shows increasing ozone loss rates from early December until the second half of January with peaking loss rates of 35 ppbv/day. Afterwards the rate of ozone loss decreased and stopped after a month. Throughout the whole winter we find accumulated ozone loss of about 1.5 ppmv at the 500 K isentrope and approximately 60 DU in the total ozone column, which is about half of the maximum loss found in past winters. From June to October 2003 an Antarctic Match campaign was carried out for the first time. About 400 sondes were launched by 9 stations. Ozone loss rates of up to 75 ppbv/day were found inside the polar vortex at the 475 K potential temperature level during the first half of September. The timing of the fastest ozone loss coincides with the return of sunlight to the vortex after the Antarctic winter. During the whole time period temperatures were low enough for PSCs, including ice clouds, to form. Results for the potential temperature range between 400 K and 550 K will be presented.
Keywords: Antarktis; ozonlaget; polarområdene; stratosfæren